Physical-chemical Characterization of Nano-Zinc Oxide/Activated Carbon Composite for Phenol Removal from Aqueous Solution - Allwar Allwar; Asih Setyani; Ulul Sugesti; Khusna Afifah Fauzani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Oil palm shell was used as a precursor for preparation of activated carbon using different chemical activations (potassium hydroxide (KOH), zinc chloride (ZNCl2), and phosphoric acid (H3PO4)). Each activated carbons (AC) was mixed with nano-zinc oxide to form a composite. From the gas sorption analyzer, it is showed that nitrogen adsorption isotherms show Type II for ZnO/AC-KOH and ZnO/AC-ZnCl2 corresponding to the micro- and mesoporous structures, respectively. However, the nitrogen adsorption isotherm of ZnO/AC-H3PO4 exhibits the Type I with predominantly microporous structures. The SEM micrographs produced unsmooth surface and different pore sizes. The XRD patterns at 2θ of 25.06° and 26.75° were come from amorphous activated carbon. The peak intensity of ZnO was weak due to low concentration of zinc precursor. However, the ZnO of ZnO/AC-ZnCl2 showed strongly peak intensity. The effectiveness of the composites was examined for phenol removal determined by UV-Vis Spectrophotometer method. The equilibrium adsorption follows the Langmuir and Freundlich models according to the best correlation coefficient (R2). The kinetic model was only obtained for the pseudo-second-order with the best linearity of the correlation coefficient (R2). The results of this study showed that the oil palm shell has a great potential for ZnO/AC with excellent adsorptive property. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).